2022
DOI: 10.21203/rs.3.rs-1543145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Effect of COVID-19 Pandemic on Emergency Surgical Care Delivery in India: A Multicenter Cross-sectional Study

Abstract: BackgroundThe COVID-19 pandemic and subsequent lockdowns adversely affected global health care services to varying extent. Emergency Services were affected along-with elective surgeries, to accommodate the added burden of COVID19 affected patients. We aimed to reflect, quantify and analyse the trends of essential surgeries and bellwether procedures during the waxing and waning of the pandemic, across various hospitals in India.MethodologyA research consortium led by WHO Collaboration Centre (WHOCC) for Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…After the COVID-19 vaccine’s introduction, this reduction was followed by an increase in the rate in 2021, with 59 patients admitted for general surgical emergencies. Our results are consistent with a previous study in which there was a reduction (59.1%) in surgical emergencies [ 24 ]; furthermore, it is reported that during the pandemic, the consultation rate for general surgery emergencies decreased significantly from 195 patients before the pandemic to 132 patients after it [ 25 ], a 54% reduction in emergency surgeries in India, while a study from Italy documented 86% decline in emergency surgery in the first month after nation-wide lockdown [ 26 - 27 ]. Likewise, a 70% downturn in surgical admissions and a 50% drop in surgeries were observed during the Ebola pandemic in Sierra Leone [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…After the COVID-19 vaccine’s introduction, this reduction was followed by an increase in the rate in 2021, with 59 patients admitted for general surgical emergencies. Our results are consistent with a previous study in which there was a reduction (59.1%) in surgical emergencies [ 24 ]; furthermore, it is reported that during the pandemic, the consultation rate for general surgery emergencies decreased significantly from 195 patients before the pandemic to 132 patients after it [ 25 ], a 54% reduction in emergency surgeries in India, while a study from Italy documented 86% decline in emergency surgery in the first month after nation-wide lockdown [ 26 - 27 ]. Likewise, a 70% downturn in surgical admissions and a 50% drop in surgeries were observed during the Ebola pandemic in Sierra Leone [ 28 ].…”
Section: Discussionsupporting
confidence: 91%